High‐throughput phenotyping reveals growth of Medicago truncatula is positively affected by arbuscular mycorrhizal fungi even at high soil phosphorus availability. Issue 5 (3rd April 2020) - Tran, Binh T. T.; Cavagnaro, Timothy R.; Jewell, Nathaniel; Brien, Chris; Berger, Bettina; Watts‐Williams, Stephanie J.
Societal Impact Statement: Arbuscular mycorrhizal fungi (AMF) may contribute to enhanced yield and nutrition of host plants for the purpose of sustainable agriculture. However, the growth response of the host plant to mycorrhizal colonization is generally only measured at harvest, and thus management decisions regarding AMF are made using only a single time point. This study highlights that AMF can provide growth benefits to the host plant over its life. Greater knowledge of how plants respond to AMF over time will improve understanding of how the association functions and ultimately lead to improved management decisions regarding AMF in an agricultural context. Summary Colonization by arbuscular mycorrhizal fungi (AMF) can result in variable responses in the growth and mineral nutrition of host plants, and is highly dependent on soil nutrient condition; limited studies have addressed the effects of AMF on plant growth over time. The aim of this study was to investigate the AMF effects on plant growth over the life of the plant, and interactions with soil phosphorus (P) and zinc (Zn) availability. We used a high‐throughput shoot phenotyping system to examine the temporal growth responses to AMF and soil P and Zn availabilities in the pasture legume Medicago truncatula . Plants were either inoculated with Rhizophagus irregularis or mock‐inoculated, and were examined under two soil P and five soil Zn availability treatments. Plants were then destructively harvested to obtain final biomass and shoot nutrition data. The growth of M. truncatula plants over time responded very differently to AMF depending on the soil P availability. At low P, projected shoot area and absolute growth rate (AGR) became increasingly greater in the mycorrhizal plants over the course of the experiment. At high P, there was a positive growth response to AMF until approximately 40 days after planting, after which the AGR of the non‐mycorrhizal plants increased and the response to AMF became neutral. Zinc availability was highly interactive with P availability, but not with AMF inoculation. This research demonstrates that growth responses to mycorrhizal fungi change over the plant's life, and are highly dependent on soil P availability. Abstract : Arbuscular mycorrhizal fungi (AMF) may contribute to enhanced yield and nutrition of host plants for the purpose of sustainable agriculture. However, the growth response of the host plant to mycorrhizal colonization is generally only measured at harvest, and thus management decisions regarding AMF are made using only a single time point. This study highlights that AMF can provide growth benefits to the host plant over its life. Greater knowledge of how plants respond to AMF over time will improve understanding of how the association functions and ultimately lead to improved management decisions regarding AMF in an agricultural context.